IMPLEMENTASI PEMBELAJARAN MULOK DAS DAN DANAU BERBASIS STEAM UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS V SDN 16 LIMBOTO - Siti Utari Mokoagow; Razak H. Umar; Aljunaid Bakari (Al-mujahidah, 2026)
This study starts from the main problem, namely "Can the implementation of STEAM-based local content learning of watersheds and lakes improve the creativity of fifth-grade students of SDN 16 Limboto?" The purpose of this study is to determine the extent to which the implementation of STEAM-based learning can improve students' creativity in the local content subject of watersheds and lakes. This study uses a classroom action research (CAR) method, with data collection techniques in the form of observation, student creativity assessment, and documentation. The results of the study showed that there was an increase in student creativity in each cycle. In cycle I, the percentage of student creativity was 44.75% with a sufficient category, then in cycle II it increased to 84.37% with a good category and had achieved the established success indicators. Based on these results, it can be concluded that the implementation of STEAM-based local content learning of watersheds and lakes can improve the creativity of fifth-grade students of SDN 16 Limboto.